Investigation on structural, morphological and luminescent properties of Mg2+-doped ZnO nanophosphors prepared by simple combustion synthesis - Rajput P.; Singh P.; Vashishtha P.; Kamni (My University, 2025)
A series of ZnO nanophosphors doped with different concentrations of Mg (x = 0–0.05) were synthesized by combustion route using urea as the fuel. The final powdered products were well characterized by using powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR), X-ray fluorescence (XRF), transmission electron microscopy (TEM), UV–visible spectroscopy (UV–Vis) and photoluminescence (PL) characterization techniques. The powder XRD patterns of the formed product shows hexagonal phase. Scherrer equation was employed to calculate the average crystallite size and was found to be in the range of 30–50 nm. XRF study confirmed the chemical analysis of the samples. The agglomerated morphology of the samples was established by the TEM studies. Band gap calculations were done with UV–visible spectroscopy. PL properties of undoped and ZnO:Mg (x = 0–0.05) using 325 nm excitation source were studied to investigate the possibility of its use for display devices. The emission spectra consisted of an excitonic band edge emission and visible emission at 500 nm corresponding to blue light. The CIE colour coordinates also correspond to the bluish-white emission. The obtained results indicated that the synthesized phosphor can be explored as a useful material for display applications. © 2021, Indian Academy of Sciences.